Formulation, characterization, and cytotoxicity evaluation of lactoferrin functionalized lipid nanoparticles for riluzole delivery to the brain - Teixeira, Maria Inês (2022)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease with a very poor prognosis. Its treatment is hindered by a lack of new therapeutic alternatives and the existence of the blood–brain barrier (BBB), which restricts the access of drugs commonly used in ALS, such as riluzole, to the brain. To overcome these limitations and increase brain targeting, riluzole-loaded nanostructured lipid carriers (NLC) were prepared and functionalized with lactoferrin (Lf), facilitating transport across the BBB by interacting with Lf receptors expressed in the brain endothelium. NLC were characterized with respect to their physicochemical properties (size, zeta potential, polydispersity index) as well as their stability, encapsulation efficiency, morphology, in vitro release profile, and biocompatibility. Moreover, crystallinity and melting behavior were assessed by DSC and PXRD. Nanoparticles exhibited initial mean diameters between 180 and 220 nm and a polydispersity index below 0.3, indicating a narrow size distribution. NLC remained stable over at least 3 months. Riluzole encapsulation efficiency was very high, around 94–98%. FTIR and protein quantification studies confirmed the conjugation of Lf on the surface of the nanocarriers, with TEM images showing that the functionalized NLC presented a smooth surface and uniform spherical shape. An MTT assay revealed that the nanocarriers developed in this study did not cause a substantial reduction in the viability of NSC-34 and hCMEC/D3 cells at a riluzole concentration up to 10 μM, being therefore biocompatible. The results suggest that Lf-functionalized NLC are a suitable and promising delivery system to target riluzole to the brain.